A study of relationship between teaching presence with cognitive and social presence in online group tasks / Mohamad Zaim Isamail, Siti Noor Ain Aziz, Norizan Othman, Syazwani Abd Rahim, Noor Hanim Rahmat and Muhamad Fikri Aziz - Isamail, Mohamad Zaim; Aziz, Siti Noor Ain; Othman, Norizan; Abd Rahim, Syazwani; Rahmat, Noor Hanim; Aziz, Muhamad Fikri (UiTM Cawangan Johor, 2024)
Group work is an effective way of learning in traditional classrooms. To foster effective involvement, academics have emphasised the need to study group interactions more closely in online learning environments. However, online classrooms have made group work more difficult during the post- pandemic period. Therefore, the study investigated how learners perceive mixed-mode group work at different stages of study. Moreover, some learners are more benefiting and more comfortable in groups expressing ideas and opinions under the direction of teachers. The data was collected via a questionnaire. The study employed a modified version of the instrument developed by earlier researchers. The questionnaire was examined using the Social Science Statistical Package (SPSS). The study surveyed 296 randomly selected participants from Universiti Teknologi MARA to investigate how learners view these three factors in mixed-method group work. The study has three main sections. Section A covers demographic profiles. Section B includes eight cognitive presence-related elements, Section C contains eight social presence elements, and Section D comprises eight teaching presence elements. A summary of findings reveals that the three subconstructs of teaching presence, cognitive presence, and social presence consumed good reliability. The Cronbach alpha for the study instrument is 0.842. The presence of teaching in these groups was discovered to have a moderate impact on the relationship between the presence of cognitive and social people in mixed group work. Thus, hybrid learning, which uses a group-work approach in classrooms, offers exciting implications for each form of presence.